An Online Relay Selection Scheme in Power Controllable Wireless Sensor Networks. (6th June 2012) - Deng, Jing; Huang, Scott C.-H.; Han, Yunghsiang S.
Abstract : We propose a data forwarding scheme termed dynamic energy-based relaying (DER) for wireless sensor networks (WSNs). In the DER scheme, all nodes try to forward their data packets toward the nodes that are optimal distance closer to the data sink. They also take the relaying node estimated lifetime into consideration in the selection process. When necessary, they will choose nodes that are closer to the data sink as relays or even the data sink itself. This distributed approach equalizes energy consumption of different relaying nodes based on their residual energy, balancing their expected lifetimes. We analyze our proposed scheme in both one-dimensional and two-dimensional networks with different setups including different residual energy, traffic rate, and network regions. Our study shows that the proposed scheme achieves a network lifetime close to the scheme based on linear programming techniques and global information or centralized processing.